Comparison of interconnection modes in the natural gas trunk pipeline network system in Western China - Ping XIE; Lei WEI; Shuoshuo SONG; Weichenzi LI (You-qi chuyun)
Objective "Trunk interconnection and regional networking" (hereinafter referred to as "interconnection") involves optimizing the allocation and transportation routes through multiple transmission schemes to address the uneven geographical distribution of gas sources in natural gas pipeline networks. Establishing crossovers between existing valve chambers along parallel pipelines is a key method for achieving this interconnection. At present, the impact of establishing such crossovers on the transmission capacity of the pipeline network during cut-off accidents remains unclear both at home and abroad, and a consensus on the arrangement of these crossovers has not been reached. Methods The model of the natural gas trunk pipeline network in Western China was developed using SPS software. The feasibility of interconnection at various valve chamber locations was evaluated for the West-East Gas Pipeline 1 and the Lunnan-Turpan Trunk Branch, the Xinjiang Section of West-East Gas Pipelines 2 and 3, and the Gansu Section of West-East Gas Pipelines 1 and 4, taking into account the design gas transmission capacity, routing, and distribution characteristics of the stations along each pipeline. Interconnection schemes for pipeline valve chambers were proposed based on feasibility and economic considerations. Based on these schemes, the influences of single (double) pipeline crossover modes on the failure length of the trunk pipeline under accident conditions, the potential reduction in gas transmission capacity, the failure frequency of crossover valves, and the stability of the gas supply system were further analyzed. Results It was recommended to adopt the double-pipeline crossover mode for the interconnection of valve chambers. The design process of "establishing the double-pipeline crossover scheme, analyzing transmission capacity under accident conditions, and conducting an economic analysis for interconnection" was summarized.Interconnection schemes were developed for the Lunnan-Kongque River Section of the West-East Gas Pipeline 1 and the Lunnan-Turpan Trunk Branch, as well as the Jinghe-Wusu Section of West-East Gas Pipelines 2 and 3. Conclusion The research findings offer a standardized design framework for the interconnection of natural gas trunk pipeline networks in China.